Nanoscale photosensitizer with tumor-selective turn-on fluorescence and activatable photodynamic therapy treatment for COX-2 overexpressed cancer cells. Issue 8 (4th February 2021) - Wang, Lan; Zhang, Yuhuan; Han, Ying; Zhang, Qi; Wen, Zhenfu; Li, Hongjuan; Sun, Shiguo; Chen, Xin; Xu, Yongqian
Abstract : A single molecule IMC-DAH-SQ  can selectively recognize tumor cells with turn-on near infrared (NIR) fluorescence and function as an adaptive photosensitizer with photodynamic therapy activity. Abstract : Effective targeting and in situ imaging-guided treatment are particularly important for accurate clinical photodynamic therapy (PDT) of malignant tumors. Herein, we propose a single molecule, named IMC-DAH-SQ, which possesses dual-targeting components, including structure-inherent targeting (SIT) and cyclooxygenase-2 (COX-2) targeting units, and controllable turn-on near infrared (NIR) fluorescence. Due to its amphiphilicity, IMC-DAH-SQ assembles into a nanoprobe with low background fluorescence. After incubation with tumor cells, the SIT and COX-2 recognition characteristics of IMC-DAH-SQ endow it with preferential tumor-targeting activity. The strong binding with overexpressed COX-2 can collapse the nanoprobe to monomers after accumulation in tumor cells, leading to turn-on NIR fluorescence that is completely different from normal cells. Additionally, benefiting from the single molecular model tactic, the nanoprobe has the advantages of simple synthesis without ever considering the loading rate and separation between the photosensitizer and targeting unit. Other favorite features, including superior biocompatibility, weak dark toxicity, and mitochondria enrichment capability, are implemented. All these traits not only afford nanoprobe precision tumor cell targeting capability but also provide promising imaging-guided antitumor therapy. We believe that the single molecular protocol will establish a novel strategy for simultaneous diagnosis and anticancer medicine treatment utilizing versatile but small compounds.